2016
DOI: 10.2174/1570159x13666151021111609
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase (HDAC) Inhibitors - emerging roles in neuronal memory, learning, synaptic plasticity and neural regeneration

Abstract: Epigenetic regulation of neuronal signalling through histone acetylation dictates transcription programs that govern neuronal memory, plasticity and learning paradigms. Histone Acetyl Transferases (HATs) and Histone Deacetylases (HDACs) are antagonistic enzymes that regulate gene expression through acetylation and deacetylation of histone proteins around which DNA is wrapped inside a eukaryotic cell nucleus. The epigenetic control of HDACs and the cellular imbalance between HATs and HDACs dictate disease state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 141 publications
(132 reference statements)
0
51
0
Order By: Relevance
“…It is also reported that inhibition of HDAC3 could induce cell autophagy in human glioma cells [ 29 ], and apoptosis in cholangiocarcinoma [ 30 ]. Besides their utilization as targets in cancer therapy, class I HDACs have gained considerable attention as targets in the search for treatments for degenerative neurological diseases, such as Alzheimer’s and Huntington’s disease [ 20 , 31 , 32 , 33 , 34 ], chronic inflammatory diseases, like asthma and COPD [ 35 , 36 , 37 , 38 ], viral infections [ 39 ], especially for human immunodeficiency virus (HIV) [ 40 , 41 , 42 ], and diabetes [ 22 , 43 , 44 , 45 ]. HDAC3, in particular, is an interesting target in Alzheimer’s disease [ 31 , 46 ], since it is reported that HDAC3 plays an important role in maintaining long-term memory for object location [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that inhibition of HDAC3 could induce cell autophagy in human glioma cells [ 29 ], and apoptosis in cholangiocarcinoma [ 30 ]. Besides their utilization as targets in cancer therapy, class I HDACs have gained considerable attention as targets in the search for treatments for degenerative neurological diseases, such as Alzheimer’s and Huntington’s disease [ 20 , 31 , 32 , 33 , 34 ], chronic inflammatory diseases, like asthma and COPD [ 35 , 36 , 37 , 38 ], viral infections [ 39 ], especially for human immunodeficiency virus (HIV) [ 40 , 41 , 42 ], and diabetes [ 22 , 43 , 44 , 45 ]. HDAC3, in particular, is an interesting target in Alzheimer’s disease [ 31 , 46 ], since it is reported that HDAC3 plays an important role in maintaining long-term memory for object location [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…HDACs are critical regulator of gene expression and HDAC inhibitors are clinically approved drugs for cancer treatment [ 131 ]. More recently, HDAC inhibitors are also explored for other conditions including neurological disorders and neurodegenerative diseases [ 132 ]. There is increasing evidence that VPA has neuroprotective properties and recent studies have shown some promising results in several animal models of neurodegenerative diseases including glaucoma, Alzheimer’s disease and Parkinson’s disease [ 91 , 133 , 134 , 135 ].…”
Section: Valproic Acid Upregulates Glial Bdnf and Ngf Leading To mentioning
confidence: 99%
“…The cellular imbalance between HAT and HDAC activity alters acetylation homeostasis causing transcriptional dysregulation which in turn provides impetus to neurodegenerative signaling (Saha and Pahan, 2006 ). Aberrant expression of HDACs has been implicated in neurologic pathologies (Ganai et al, 2016 ). For instance, HDAC6 overexpression has been reported to inhibit nerve growth by deacetylating tubulin protein (Rivieccio et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%